Effect of Trading Days on Precious Metals and Stock Returns During COVID-19 and the Russia-Ukraine War - Yunanto, Arif; Robiyanto, Robiyanto; Harijono, Harijono (Journal of Accounting, Entrepreneurship and Financial Technology (JAEF), 2025)
This study was conducted to determine the returns generated during trading days in the commodity market and the stock market. The efficient market theory says that the return generated is the same every day. However, some studies have found positive and negative returns that occur on different days for each research period. The COVID-19 pandemic has affected the economic condition of a country. In addition, geopolitical conditions will also affect trade cooperation between countries. The method used in this study is GARCH (1,1) with data taken during the COVID-19 pandemic and the Russia-Ukraine war. The samples used in this study are the Jakarta Composite Index (JCI) and precious metal commodities. Precious metals are represented by gold, silver, platinum, and palladium. The results show that during the COVID-19 pandemic, the JCI, Platinum, and Palladium were proven to have a day-of-the-week effect. During the Russia-Ukraine War, there was no day-of-the-week effect.